Rubiaceae do Parque Nacional do Iguaçu, Paraná, Brasil - Toderke, Marlene Livia (2015)
The Iguaçu National Park (ParNa Iguaçu), with Semideciduous Forest and Araucaria Forest, represents the largest fragment of the Atlantic Forest in the interior of Parana. Has been extremely devastated over the years and the Park has approximately 185.000 ha, which equivalent to 4% of the state's original vegetation. Rubiaceae is among the ten largest families in number of species and also has a high number of endemism in the Atlantic Forest. This work was divided into two sections, the first being a floristic inventory of Rubiaceae and similarity of areas within the ParNa Iguaçu. The Park was divided into three areas for this study: Capanema, located in the south with Forest Semideciduous; Céu Azul, farther north, with transition between Semideciduous Forest and Araucaria Forest and the region of Foz do Iguaçu, southwest of the park, with Semideciduous Forest. The analysis showed that the areas of Capanema and Foz do Iguaçu have about 80% similarity. In the second chapter we present identification keys, descriptions and illustrations, as well as taxonomic and ecological comments and distribution of the species. We identified 26 species in 13 genera, Psychotria being the most diverse, with five species, followed by Borreria, Galianthe, Manettia and Palicourea with three species each, Geophila with two species, and the other genera, Coccocypselum Coussarea, Diodia, Faramea, Hamelia, Richardia and Spermacoce with only one species each.